From fork to farm: understanding Kitwe's food system through the fish lens - Siyanga-Tembo, Fridah (Department of Environmental and Geographical Science, 2018)
Food production has been a constant feature of food security policies. This narrative has continued despite findings showing that food insecurity is structural, and more driven by issues of access than availability, particularly for low-income households in cities who live in a cash economy. While usually considered a rural issue, the urban poor with low and unreliable incomes also face food insecurity which manifests differently to that of their rural counterparts. Thus, this creates the need to understand how the urban poor get their food. Garneton, a low-income area in Kitwe, Zambia, was chosen as the case study area for understanding the food system that feeds the urban poor. Fish and the fish value chain were used as the lens with which to understand the food system. The primary aim of the study was to understand the flow of fish in the food system and how it gets to low-income households in Kitwe. A qualitative methodology using semi-structured in-depth interviews was used. A bottom up and systems approach which started by finding out what the low-income consumers ate, and following the fish value chain systematically up to the producers enabled the study to capture the actual food system that feeds the poor and uncovered the different issues affecting the food system. The study had three main findings. The first finding was that the low-income households bought their food from both formal and informal markets but were more highly dependent on the informal markets. The factors that drove their purchasing decisions included income, proximity and volumes of fish sold. Secondly, the study also found that informal traders bought their fish mainly through the informal markets although the imported fish was bought from the formal market. Thirdly, the study found that there were a number of factors that affected the food system. These included policy, economic and environmental factors. The pathways of fish were also found to change in accordance with the fish ban. The thesis argues that, there is greater need to have policy that addresses the needs of the urban poor. Food should also be looked at as a cross cutting issue with different food systems perceived as complementing each other to addressing the food needs, particularly of the urban poor. Finally, more attention must be paid to the informal market which plays a significant role in meeting the food security needs of the urban poor.